STAG2 regulates polycomb and differentiation in urothelial precursors and bladder cancer - Youngrok Park; Wanying Xu; Tianyi Yang; Victoria Hill; Xiaoyuan He; Lisa Sadzewicz; Luke Tallon; Jung-Sik Kim; Fulai Jin; Todd Waldman (PLoS ONE, 2025)
The STAG2 tumor suppressor gene is commonly inactivated by mutations in a wide range of common cancer types. STAG2 encodes a component of the cohesin complex, which controls sister chromatid cohesion and 3D genome organization. In bladder cancer, STAG2 mutations are most common in the earliest low-grade lesions, suggesting that mutational inactivation of STAG2 may be an initiating event. To provide insight into the mechanisms of STAG2 tumor suppression in bladder cancer, siRNA and shRNA were used to knock down STAG2 in several different human non-neoplastic bladder cancer precursor cell lines. Gene editing was used to generate cultured human cancer cell lines that differ only in the presence or absence of bladder-cancer derived STAG2 mutations. These systems were interrogated using RNA-seq, Western blot, and qRT-PCR before and after induced differentiation. We find that inactivation of STAG2 in bladder cancer cells and in bladder epithelial precursor cells resulted in concomitant inactivation of the H3K27me3 Polycomb chromatin mark. Inactivation of STAG2 also attenuated induced differentiation of bladder epithelial precursor cells. STAG2 and other components of cohesin were upregulated during this differentiation process. This study provides new insights into the role of STAG2 in the pathogenesis of bladder cancer, demonstrating roles for STAG2 in the regulation of Polycomb-mediated epigenetic regulation and in the differentiation of bladder epithelial precursor cells.